VIRTUE EDUCATION IN SUFFERING FROM SEXUAL VIOLENCE - Chatarina Suryanti; Roberto Reno Sitepu (P3TK, Sanata Dharma University, 2023)
Is education on theological virtues and moral virtues still relevant to help victims of sexual violence? This article was written to see the importance of education on theological and moral virtues to help victims of sexual violence. The method used for research includes descriptive qualitative research which is carried out by combining field research and literature. Based on the research conducted, it was found that all respondents stated that education on theological virtues and moral virtues was still relevant to helping sufferers because of sexual violence. Therefore, a concept of personal theological and moral virtue is needed as a strategy to maintain and develop the integrity of creation and to experience oneself as the image of God.